The Effect of Using Collaborative Strategic Reading (CSR) Toward Students Reading Comprehension at Eleventh Grade of SMA Negeri 1 Banuhampu - Wanda Azizah; Elsi Amiza; Merry Prima Dewi; Syahrul Syahrul (Education Achievement: Journal of Science and Research, 2024)
This research aims to explain the effect of using Collaborative Strategic Reading (CSR) on students' reading comprehension in the eleventh grade of SMA Negeri 1 Banuhampu. To explain the effect, researchers used experimental research with a quasi-design. The location of this research was taken in class XI of SMA Negeri 1 Banuhampu with a sample size of 70 students. Based on this text, researchers found a significant effect of using Collaborative Strategic Reading on students' reading comprehension, with results of Sig. (2-tailed) is 0.000 < ½ ? (0.025). It can be concluded that there is an influence produced by the use of CSR in reading comprehension. This research also looks at the difference in average scores in the post-test results of the two classes, where the experimental class score is higher than the control class with a score of 72.31 > 68.53 with a comparison score of 3.78. It can be ascertained that the research conducted by researchers produced results in seeing differences in the use of Collaborative Strategic Reading (CSR) on students' reading comprehension.